Assessing the development gap - Irina Sinitsina; Alexander Chubrik; Irina Denisova; Vladimir Dubrovskiy; Marina Kartseva; Irina Makenbaeva; Magdalena Rokicka; Michael Tokmazishvili (Center for Social and Economic Research (CASE), 2007)
Current report aims to identify major existing gaps in the four socio-economic dimensions (economic, human, environmental, and institutional) and to reveal those gaps which could potentially hinder social and economic integration of neighbor states with the EU. To achieve this, the authors aim to assess the existing trends in the size of the gaps across countries and problem areas, taking into consideration the specific origin of the gap between EU15/EU12, on the one hand, and FSU republics, EU candidates and West Balkan countries, on the other hand. The paper is structured as follows: (1) An analysis of the historic roots and origins of the development gap, and its evolvement over time. (2) A review of literature sources, draft analysis of primary statistical data, and qualitative explanations of gaps and divergences in selected development issues across four socio-economic dimensions: * level of economic development and convergence rates based on real GDP (application of methodology testing β and σ convergence to the set of countries analyzed); * quality of life and its components (poverty, inequality, health status and Heath care, access to fresh water and sanitation facilities, subjective perceptions of well-being); * human capital and labor market development, including level of education and public spending on education, its accessibility and quality, main differences in labor market development (employment participation rates and levels of unemployment, new jobs creation and labor protection legislation); * innovation potential, including R&D, information and communication technologies, and institutional environment; * environmental performance in terms of environmental stresses, efforts aimed at their reduction, and institutional capacity; * business climate, political institutions, and other institutional indicators (econometric analysis). (3) A test econometric analysis of development gaps across selected dimensions by using a Principal Components Method (PCM). The results are further presented in the form of ranks of countries analyzed reflecting their distances from EU15 in respective aggregate averages. Special attention is paid to gender-related development issues. Respective issues in human capital and labor market study, as well as variables included into PCM analysis were supplemented with relative gender data. Several preliminary conclusions finalize the report.
Keywords: O11; O52; O57; P27; 330; EU; CIS; development gap; GDP; convergence; quality of life; human capital; innovation; environment; institutions; Principal Components Method; Entwicklungskonvergenz; Schätzung; EU-Staaten; EU-Mitgliedschaft; Transformationsstaaten